Analysis of appearance of rowers of light-weight on XXIX and XXX games of Olympiads - Омельченко [Omel’chenko O.], Олена Станиславівна (Slobozhanskyi Herald of Science and Sport, 2012)
<!--[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]--> Passing of competition distance is examined the rowers of light-weight on ХХIХ that the XXX Оlympicgames. For an analysis the results of passing of competition distance are offered in the class of boats two is pair womanish light-weight, two is pair masculine light-weight and masculine four without steering light-weight. The comparative analysis of passing of competition distance of crews, gettings in the finale of the Olympic games in Beijing in 2008 and in the finale of the Olympic games in London in 2012 is done. Conformities to the law of change of temporal descriptions of passing of distance are exposed in a boat-racing. Determine which countries are the leaders in training winners in rowing at light weight. <!--[if gte mso 9]> <![endif]--><!--[if !mso]> <![endif]--><!--[if gte mso 10]> <![endif]-->